Prevalence and patterns of antibiotic use among inpatients in antimicrobial resistance surveillance hospitals in Malawi: a 2021 multisite point prevalence survey - Ronald Chitatanga; Chikhulupiliro Yiwombe; Gracian Harawa; Daniel Namalawe; Kholiwe Katengeza; Silva Benito; Innocent Chibwe; Hope Chadwala; Oscar Divala; Alinafe Kawerama; Harry Milala; Dzinenani Maziya; et al. (Journal of Health, Population and Nutrition, 2026)
Abstract Background Antimicrobial resistance threatens global health and is largely driven by inappropriate antimicrobial use. In Malawi, infectious diseases remain the leading health burden, fueling high antibiotic consumption. However, systematic data on antibiotic prescribing practices are scarce. This study evaluated the prevalence and pattern of antibiotic use for inpatients admitted in hospitals participating in Malawi’s antimicrobial resistance sentinel surveillance network. Methods A multisite point prevalence survey on antibiotic use was conducted in June 2021 across seven hospitals in the sentinel surveillance network: Queen Elizabeth Central Hospital, Zomba Central Hospital, Kamuzu Central Hospital, Mzuzu Central Hospital, Mangochi District Hospital, Mzimba South District Hospital, and Malamulo Adventist Hospital. Antibiotic prescription data was collected from randomly selected patient medical records using the World Health Organization methodology for point prevalence surveys on antibiotic use. Four domains were described: antibiotic-use prevalence, patterns of antibiotic use, local guideline compliance, and microbiology diagnostic service use. Results A total of 1,030 eligible patient files were reviewed across the surveyed hospitals, of which 46.1% (475/1030; 95% CI: 43.1–49.2) were patients on antibiotics. 51% (244/475) of the patients on antibiotics were prescribed only one class of antibiotic while the remainder had more than one. Among patients using antibiotics, 724 prescriptions were analyzed. The three most frequently prescribed antibiotics were ceftriaxone (36.5%), metronidazole (20.6%), and benzylpenicillin (14.8%), together accounting for over 70% of all prescriptions. Overall, 58.7% of prescriptions were Access category agents, while 41.3% were in the Watch category; no Reserve category agents were prescribed. The most common indications were prophylaxis (unspecific) (17.3%; 125/724), clinical sepsis (17.1%; 124/724), and pneumonia (12.8%; 93/724). Compliance to the Malawi Standard Treatment Guidelines ranged from 58% at Zomba and Kamuzu Central Hospitals to over 90% at Mzuzu Central and Mzimba South District Hospitals. Prescribing was predominantly empirical, with more than 95% empirical therapy at most sites, apart from Queen Elizabeth Central Hospital (39%) and Malamulo (10%). Conclusion These baseline findings from antimicrobial resistance surveillance hospitals in Malawi highlight opportunities to strengthen antimicrobial stewardship through more appropriate antibiotic selection, greater use of Access category antibiotics where clinically indicated, and improved integration of microbiology services into prescribing decisions.